Electromagnetic fields as structure-function zeitgebers in biological systems: environmental orchestrations of morphogenesis and consciousness - Rouleau, Nicolas; Dotta, Blake T. (Frontiers in Integrative Neuroscience, 2014)
Within a cell system structure dictates function. Any interaction between cells, or a cell and its environment, has the potential to have long term implications on the function of a given cell and emerging cell aggregates. The structure and function of cells are continuously subjected to modification by electrical and chemical stimuli. However biological systems are also subjected to an ever-present influence: the electromagnetic environment. Biological systems have the potential to be influenced by subtle energies which are exchanged at atomic and subatomic scales as electromagnetic phenomena. These energy exchanges have the potential to manifest at higher orders of discourse and affect the output (behaviour) of a biological system. Here we describe theoretical and experimental evidence of electromagnetic influence on cells and the integration of whole systems. Even weak interactions between electromagnetic energies and biological systems display the potential to affect a developing system. We suggest the growing literature of electromagnetic effects on biological systems has significant implications to the cell and its functional aggregates.